PENERAPAN ANALISIS KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN JANGGELAN DI KABUPATEN PACITAN - Supriyadi Supriyadi; Joko Winarno; MMA. Retno R.; Sumani Sumani (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
Land suitability for particular uses is usually evaluated using land characteristics or land quality. Land suitability is crucial to determining the success of a plant's production. Janggelan plants are potential commodities that are potential to be developed. Technological opportunities and innovations in the development of Janggelan are very wide open, both as a source of food, biopharmaceutical, industrial, and trade. The cultivated land has been exported to Thailand, Vietnam and China in dry form. However, during this time, janggelan plants have not been developed and only planted as side crops in agroforestry. The purpose of this activity is the development of janggelan plant based on land suitability analysis in Pacitan Regency and increase the production of grass jelly in Pacitan regency.Keywords : janggelan, land suitability, Pacitan.